2000
DOI: 10.1182/blood.v96.9.3029
|View full text |Cite
|
Sign up to set email alerts
|

Generation of murine dendritic cells from flt3-ligand–supplemented bone marrow cultures

Abstract: Murine dendritic cells (DCs) can be classified into at least 2 subsets, “myeloid-related” (CD11bbright, CD8α−) and “lymphoid-related” (CD11bdull, CD8α+), but the absolute relationship between the 2 remains unclear. Methods of generating DCs from bone marrow (BM) precursors in vitro typically employ granulocyte-macrophage colony-stimulating factor (GM-CSF) as the principal growth factor, and the resultant DCs exhibit a myeloidlike phenotype. Here we describe a flt3-ligand (FL)–dependent BM culture system that g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
137
1
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(147 citation statements)
references
References 47 publications
6
137
1
3
Order By: Relevance
“…A characteristic feature of TLR‐induced DC activation is increased cell surface expression of T‐cell co‐stimulatory molecules and MHC class II 13 , 32 . To establish whether ISCOMATRIX adjuvant directly activated DCs, we generated DCs in vitro using the FMS‐like tyrosine kinase 3 (Flt3) ligand culture system 33 , 34 . Compared with TLR4 (lipopolysaccharide, LPS) or TLR9 (CpG) stimulation, ISCOMATRIX adjuvant failed to induce CD40, CD69, CD80 or MHC class II expression (Figure 5a and data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…A characteristic feature of TLR‐induced DC activation is increased cell surface expression of T‐cell co‐stimulatory molecules and MHC class II 13 , 32 . To establish whether ISCOMATRIX adjuvant directly activated DCs, we generated DCs in vitro using the FMS‐like tyrosine kinase 3 (Flt3) ligand culture system 33 , 34 . Compared with TLR4 (lipopolysaccharide, LPS) or TLR9 (CpG) stimulation, ISCOMATRIX adjuvant failed to induce CD40, CD69, CD80 or MHC class II expression (Figure 5a and data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Maturing LC en route to the lymph node up‐regulate CD8α expression 95 . The same is also true for BM‐derived DC activated with LPS or IFN‐α 96 . Recently it was shown that a proportion of purified splenic CD8α − DC can up‐regulate CD8α, CD205 and CD24 following intravenous injection into mice 97 .…”
Section: The Lineage Relationship Of Dendritic Cells With Other Myelomentioning
confidence: 94%
“…Flt3‐ligand supplemented bone marrow cell cultures were generated as described with slight modification 37. Briefly, bone marrow cells were flushed out of femurs and tibiae,centrifuged and red blood cells were lysed for 2 min with tris‐ammonium chloride at 37°C.…”
Section: Methodsmentioning
confidence: 99%